Discourse markers in Shajara-i Tarākima - Kahya, Hayrullah (SPRINGERNATURE, 2025)
Shajara-i Tar & amacr;kima, transcribed in Classical Chagatai Turkic by Abu al-Ghazi Bahadur Khan during the 17th century, is one of the most significant works in Turkology studies. Since the 19th century, it has garnered substantial interest among Turkology researchers from various nations, becoming the subject of numerous scholarly investigations. However, these studies have primarily focused on critiquing and revising the previous researchers' works, overlooking the characteristics of spoken language present in the text. Nevertheless, considering that the fundamental basis of the work lies in oral narratives, it is evident that the text incorporates abundant features of colloquial language. Therefore, a pragmatic evaluation of the Shajara-i Tar & amacr;kima is crucial to better comprehending and interpreting the work. This study analyzes the discourse markers in the Shajara-i Tar & amacr;kima to achieve this purpose. The research builds upon the new model proposed by Crible and Degand (2019), which identifies discourse markers based on their combination of domain and function. The study asserts that in intralingual or interlingual translations of historical texts containing features of colloquial language, discourse markers play a vital role in ensuring the accurate transfer of meaning.
Keywords: Arts & Humanities - Other Topics; Social Sciences - Other Topics